Long noncoding RNA LINC00052 inhibits colorectal cancer metastasis by sponging microRNA‐574‐5p to modulate CALCOCO1 expression. Issue 10 (19th May 2019) - Yu, Gangfeng; Xiong, Dongmei; Liu, Zhengshu; Li, Yongguo; Chen, Ke; Tang, Hua
Abstract: The dysregulation of long‐chain noncoding ribonucleic acid (lncRNA) is a common phenomenon in many human cancers. Some studies on the biological function of long intergenic non‐protein‐coding RNA 52 (LINC00052) in cancer indicate that this gene can act as either oncogene or tumor suppressor in some kinds of cancers, such as breast cancer, gastric cancer, liver cancer, and lung cancer. However, the biological function of LINC00052 in colorectal cancer (CRC) has not been studied. Quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR) and Western blot (WB) techniques were applied to detect the expression levels of LINC00052, miR‐574‐5p, and calcium‐binding and coiled‐coil domain 1 (CALCOCO1) in CRC cells and tissues. We authenticated the biological function of LINC00052 and miR‐574‐5p in CRC, and find some target genes for LINC00052 and miR‐574‐5p via bioinformatics methods. Dual‐luciferase reporter gene assay was performed to identify the interaction between LINC00052 and miR‐574‐5p or CALCOCO1 and miR‐574‐5p. The results demonstrated that LINC00052 was downregulated in CRC tissues compared with their adjacent tissues. And LINC00052 could suppress CRC cells metastasis both in vivo and in vitro. Beyond that, miR‐574‐5p was upregulated in CRC tissues, and as an oncogene, it accelerated CRC cell migration and invasion. More importantly, the results of our research demonstrated that LINC00052 could regulate the expression of CALCOCO1 via sponging miR‐574‐5p in CRC. Overall, our study illuminated the lncRNA‐miRNA functional networks in CRC, and these results might provide a new research direction for the diagnosis and treatment of CRC. Abstract : 1. A new long‐chain noncoding ribonucleic acid (LncRNA), LINC00052, was aberrantly downregulated in colorectal cancer (CRC) tissues and CRC cells. 2. LINC00052 inhibited CRC cell migration and invasion in vitro and in vivo. 3. miR‐574‐5p was a downstream target of LINC00052. Overexpression of miR‐574‐5p could promote CRC cells migration and invasion. 4. LINC00052 could act as an endogenous sponge by binding to miR‐574‐5p and reduce miR‐574‐5p expression. 5.miR‐574‐5p could regulate CALCOCO1 by interacting with its 3′UTR. LINC00052 modulates the repression of CALCOCO1 by binding to miR‐574‐5p to inhibit migration and invasion of CRC.